PEMBELAJARAN PAUD DIMASA PANDEMI COVID-19 - Milda, Jevi (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2022)
The COVID-19 pandemic has had an impact on the implementation of learning at the PAUD level. The purpose of this study was to determine the learning process carried out at TK Dharma Wanita 1 and 2 Sekaralas, Widodaren, Ngawi. This research is a type of qualitative descriptive research. The research subjects were Dharma Wanita 1 and 2 Sekaralas Kindergarten teachers and 10 parents and guardians of students. Data collection techniques were carried out by observation and interviews. The results showed that the online learning system was difficult to implement in Dharma Wanita 1 and 2 Sekaralas Kindergartens because of several factors, namely teacher readiness, parental readiness, and student readiness. Internet network facilities are not yet stable in the Sekaralas Village area so that not all students are able to take distance learning. Parents of Dharma Wanita 1 and 2 Kindergarten students have a low level of understanding of technology so they are less able to accept teacher directions to guide children to study at home. The response of children when online learning is passive and complains of being bored.